Investigation Digital Game Addiction Awareness of Faculty of Health Sciences Students - Egemen MANCI; Onur Mutlu YAŞAR; Hazal YAKUT OZDEMIR; Buse ULUCAN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
Digital games have become an important platform and leisure activities where people spend their time with the widespread use of the internet and the increase in connection speed. Since digital games are accessible anytime and anywhere and do not require people to be physically together, it is argued that their popularity has increased significantly and reached the level of addiction, especially among today's youth and with the effect of factors such as the pandemic. The aim of this study is to determine the digital game addiction awareness of health sciences faculty students. The study was done using the relationship model, which is one of the quantitative research methodologies. This study included 344 university students studying in the Sports Sciences, Physical Therapy and Rehabilitation, Nutrition and Dietetics, and Nursing Departments at the Faculty of Health Sciences. The Awareness of Digital Game Addiction Scale (DOBİFÖ)" was used to collect data. The parametric tests were used in data analysis. Based on the findings of our study, it is seen that students studying in the field of health sciences have a high awareness of digital game addiction (X¯= 3.85). The nutrition department shows the highest level of awareness compared to other departments. In addition, it was observed that female students had higher levels of awareness than males. It was also observed that the awareness of those who do not play digital games was higher.